The Challenges and Strategies of Coastal Tourism Development:The Insight from Kampai Island, Indonesia - Iromi Ilham; Abdullah Akhyar Nasution; Muh. Fahrudin Alawi; Richa Meliza; Tri Yuwana Oktaviani; Khairunnisa Hasibuan; Septriani Septriani (Jurnal Ilmiah Peuradeun, 2026)
While leveraging local potential is an established paradigm for sustainable tourism, its application in geographically isolated contexts remains complex and underexplored. This study addresses this gap by examining the unique case of Kampai Island, Indonesia, a remote destination possessing underutilized natural and cultural assets. The objectives of this research are: 1) to identify the island’s tourism potential and development challenges; and 2) to formulate comprehensive strategies for sustainable growth. Utilizing a phenomenological qualitative design, data were gathered through participant observation, in-depth interviews, and document analysis. The findings highlight significant potential in natural features such as Berawe Beach, as well as cultural-historical sites including the Keramat Panjang and Mas Merah cemeteries. However, development efforts are hindered by multidimensional barriers, encompassing inadequate infrastructure, limited institutional capacity, a lack of strategic partnerships, and human resource limitations. Synthesizing these insights, the discussion proposes an integrated strategic framework. Key recommendations involve strengthening local institutions and human resources through context-specific training, fostering multi-stakeholder collaborations to leverage external resources, prioritizing participatory infrastructure development, and designing integrated tourism products based on local narratives. In conclusion, sustainable tourism on remote islands requires a holistic approach that strategically leverages local assets and addresses systemic constraints via inclusive and collaborative planning.